The Impact of Microeconomic Variables on Sustainable Infrastructure Development in Nigeria - Mbazor, D. N.; Thwala, D. W. (International Journal of Real Estate, 2025)
The link between micro-economic variable and infrastructure development is central in determining the pace and sustainability of national growth and development, especially in terms of economic volatility. This study examines the impact of key micro-economic variables, such as interest rates, inflation, exchange rate and employment levels, on infrastructure development in Nigeria. A sample size of 150 respondents, comprising experts in the financial sector, policy makers, professionals in the construction industry and economists, were selected to provide comprehensive view on the subject. Methods used for data collection included a mix of surveys, interviews, and analysis of basic economic indicators. The study employed multiple regression analysis to assess the relationship between these variables and infrastructure outcomes, while qualitative data, on the other hand, was analyzed using thematic analysis method. This involves identifying, analysing, and reporting patterns (themes) within the data. Findings reveal a significant correlation between micro-economic instability, such as high inflation and fluctuating exchange rates, and delays or cost overruns in infrastructure project development.  conclusively, the study highlights the need for adaptive economic policies that considers microeconomic uncertainties to foster sustainable infrastructure development. The results provide practical insights for policy makers and investors aiming to mitigate the adverse effects of economic uncertainties on infrastructure development initiatives.
Keywords: infrastructure development; emerging economies; microeconomic factors; sustainable infrastructure; Economic uncertainty